Synthesis and characterization of organoclay modified with cetylpyridinium chloride - Banik, N; Jahan, SA; Mostofa, S; Kabir, H; Sharmin, N; Rahman, M; Ahmed, S (Bangladesh Journal of Scientific and Industrial Research, 2015)
Bentonite has been subjected to modification through ion-exchange reaction by 1-cetylpyridinum chloride. The modified samples were studied by X-ray diffraction (XRD) technique, Fourier transform infrared (FT-IR) spectroscopy and scanning electron microscopy (SEM). The basal spacing of unmodified bentonite, determined by XRD was 14.99 Å and after modification it increased up to 16.97 Å and 16.22 Å at 1CEC and 2CEC. The FT-IR studies revealed structural differences between the modified and unmodified bentonite samples. The IR spectra of the modified bentonite showed the C-C stretching bands (1465 and 1462 cm-1) and C-H vibrations (near 2926 and 2852; 2854 cm-1). Results of the SEM study revealed a tendency towards lump formation and agglomeration of the organomodified clay particles of bentonite. The possibility of the use of new organoclay to adsorb oils from aqueous solution will be explored. Bangladesh J. Sci. Ind. Res. 50(1), 65-70, 2015